1998
DOI: 10.1073/pnas.95.11.6367
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin gene transfer: Inhibition of tumor growth in vivo by blockage of endothelial cell proliferation associated with a mitosis arrest

Abstract: The antitumoral effects that follow the local delivery of the N-terminal fragment of human plasminogen (angiostatin K3) have been studied in two xenograft murine models. Angiostatin delivery was achieved by a defective adenovirus expressing a secretable angiostatin K3 molecule from the cytomegalovirus promoter (AdK3). In in vitro studies, AdK3 selectively inhibited endothelial cell proliferation and disrupted the G 2 ͞M transition induced by M-phasepromoting factors. AdK3-infected endothelial cells showed a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
147
2
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(158 citation statements)
references
References 26 publications
(29 reference statements)
7
147
2
2
Order By: Relevance
“…Similarly, tumor treatment with other antiangiogenic gene transfer such as angiostatin, endostatin, and platelet factor-4 also led to reduced tumor size with inhibiting tumorassociated vascularization. [17][18][19] Together with other reports, our data suggested that the delivery of the antiangiogenic genes could constitute an attractive solution to problems that resulted from the usage of recombinant proteins. [17][18][19] The present data provide the first demonstration that viral vector-based delivery of the cDNA for NfTSP2 can be used to modulate the tumor growth in the in vivo mouse tumor model.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, tumor treatment with other antiangiogenic gene transfer such as angiostatin, endostatin, and platelet factor-4 also led to reduced tumor size with inhibiting tumorassociated vascularization. [17][18][19] Together with other reports, our data suggested that the delivery of the antiangiogenic genes could constitute an attractive solution to problems that resulted from the usage of recombinant proteins. [17][18][19] The present data provide the first demonstration that viral vector-based delivery of the cDNA for NfTSP2 can be used to modulate the tumor growth in the in vivo mouse tumor model.…”
Section: Discussionsupporting
confidence: 79%
“…27 Cell cycle regulatory proteins that are critical to endothelial cell proliferation such as M-phase phosphoproteins have recently been shown to be downregulated by angiosatin. 28 Furthermore, an angiostatin-endostatin fusion gene showed significantly greater inhibition of human umbilical vein endothelial cell tube formation in vitro and potent antitumor effects in a melanoma model in vivo, than angiostatin, endostatin, or a combination of the two genes. 20 In our experiments, transfection with angiostatin gene first and endostatin gene later was inefficient, whereas reverse order induced a significant antitumor effect.…”
Section: Low-voltage Ep and Antiangiogenic Gene Therapy M Uesato Et Almentioning
confidence: 96%
“…7 Angiostatin has been described to exert potent antiangiogenic and antitumor activities in a variety of murine tumor models. [7][8][9][10] Similarly, a 20-kDa (184 amino acid (aa)) C-terminal fragment of collagen XVIII, termed endostatin (ES), is reported to be a potent inhibitor of tumor angiogenesis and micrometastases development. 5,11 The urokinase plasminogen activator (uPA) binds to its receptor uPAR via its light chain fragments, 12 known as amino-terminal fragment ATF (residues .…”
Section: Introductionmentioning
confidence: 99%